Digital image characteristics for enhanced interpretation in child sexual violence case examinations - Budiningsih, Yuli; Purwadianto, Agus; Yudhistira, Aria; Budiarso, Agusalam (Faculty of Medicine Universitas Indonesia, 2024)
BACKGROUND Photography is an integrated part of standard forensic examination procedures, acting as a guide and the evidence itself. Despite its potential, no research has yet explored the use of 35mm format cameras (digital single-lens reflex [DSLR]) in sexual violence cases. This study aimed to assess the impact of DSLR camera image characteristics on the interpretation of child sexual abuse cases. METHODS This cross-sectional study used 55 digital photos selected through a convenience sampling. The samples were interpreted by two independent forensic experts who were not affiliated with this research and were compared with the results of the doctor’s examination from the medical records. RESULTS The metadata extraction results (EXIF data) indicated that all characteristic values had an abnormal distribution. The digital photos’ characteristics were associated with the use of a 50mm focal length (p = 0.011). A range of lens opening values (aperture = f7.1–f8.0), shutter speed (1/100–1/125 sec), and sensor sensitivity (ISO = 800–1600) were not associated with the experts’ interpretation conformity. Additionally, the conformity index for the overall interpretation by the two forensic experts differed in each area. CONCLUSIONS Focal length of 50mm was significantly related to interpretation conformity. The exposure triangle settings, including aperture (f7.1–f8.0), shutter speed (1/100–1/125 sec), and ISO (800–1600), can serve as fundamental guidelines for digital camera settings in examining child sexual violence cases.